THE APPLICATION OF INTERNET TECHNOLOGY AND SMS GATEWAY FOR MEMBER DATA MANAGEMENT AND INFORMATION DISSEMINATION OF PERTUNI CENTRAL JAVA - Hestiningsih, Idhawati; Mardiyono, Mardiyono; Sukamto, Sukamto; Handoko, Slamet; N, Ari Sriyanto (Journal of Community Research and Service, 2017)
Abstract Pertuni member data (Indonesian Blind Union) of Central Java has not been managed well, so when the institution requesting the data for researching and empowering for the blind within the country or abroad, Pertuni party can not give the accurate data. Information delivery is still using the letter sent through post office which will take a long time, so it will often lead the miscommunication and delay of the information between the board and members of the branch. The purpose of this activity is the provision of facilities supporting media data management and information dissemination member of Pertuni Central Java so it will have the better management. The results of these activities are Pertuni Central Java has the member information system and SMS Gateway system which can easily accessed by the blind.Keywords:  blind, member information system, SMS Gateway